The impact of the Practical Turn of Philosophy in Argentina, didactic drifts - Atencio Noguera, Pablo Alfredo (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The article is born within the framework of a thesis project of the Doctorate in Philosophy (Resolution No. 0384/2022 - FFHA: “Linkage didactics in Philosophy as a transdisciplinary practice”), in coordination with the creation of the Free Chair (Resolution No. 096/2021 – FFHA: “The Practical Turn of Philosophy”) of the Faculty of Philosophy, Humanities and Arts, of the National University of San Juan (Argentina); both proposals belong to the author of this work, in which it is intended to problematize the impact of the Practical Turn of Philosophy (still in the process of legitimation), in Argentina; for recognize possible didactic drifts.